Preoperative carbohydrate loading before elective abdominal surgery: A systematic review and network meta-analysis of phase II/III randomized controlled trials. Issue 2 (February 2022) - Ricci, Claudio; Ingaldi, Carlo; Alberici, Laura; Serbassi, Francesco; Pagano, Nico; De Raffele, Emilio; Minni, Francesco; Pironi, Loris; Sasdelli, Anna Simona; Casadei, Riccardo
Summary: Background & aims: The preoperative use of carbohydrate loading (CHO) is recommended in patients undergoing abdominal surgery, even if the advantages remain debatable. The aim was to evaluate the CHO benefits in patients undergoing abdominal surgery. Methods: A systematic search of randomized clinical trials was made. A frequentist random-effects network meta-analysis was carried out, reporting the surface under the cumulative ranking (SUCRA). The primary endpoint regarded the morbidity rate. The secondary endpoints were aspiration/regurgitation rates, the length of stay (LOS), the rate of postoperative nausea and vomiting (PONV), the changes (Δ) in insulin sensitivity or resistance, and the postoperative C- reactive protein (CRP) values. Results: CHO loading and water administration had a similar probability of being the approach with a lower morbidity rate (SUCRA = 62.4% and 64.7%). CHO and clear water also had a similar chance of avoiding the PONV (SUCRA of 80.8% and 77%). The aspiration regurgitation rate was not relevant in non-fasting patients (0.06%). CHO administration was associated with the shorter hospitalization (SUCRA 86.9%), with the best metabolic profile (SUCRA values for insulin resistance and sensitivity were 81.1% and 76%). CHO enriched was the best approach for postoperative CRP values. Preoperative fasting was the worst approach for morbidity, PONV, insulin resistance and sensitivity, and CRP (SUCRA values of 32.1%, 21.7%, 10.2%, 3.2%, and 2.0%). Conclusion: Both preoperative CHO loading and clear water use were superior to the fasting about morbidity. CHO drinks use could provide specific advantages, reduce the PONV rate, and improve carbohydrate homeostasis, inflammatory pathway, and hospitalization.